2007
DOI: 10.1002/per.618
|View full text |Cite
|
Sign up to set email alerts
|

The intervening role of social worldviews in the relationship between the five‐factor model of personality and social attitudes

Abstract: The present research investigates in a student (N ¼ 183) and a voter sample (N ¼ 276) whether the relationships between the Five-Factor Model (FFM) personality dimensions and social attitudes (i.e. Right-Wing Authoritarianism [RWA] and Social Dominance Orientation [SDO]) are mediated by social worldviews (i.e. dangerous and jungle worldviews). Two important results were obtained. First, the perception of the world as inherently dangerous and chaotic partially mediated the relationships of the personality dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 52 publications
6
83
0
2
Order By: Relevance
“…If our data were comparable with those found by Van Hiel, Cornelis, and Roets (2007) and by Sibley and Duckitt (2009), Openness should negatively influence RWA (HP1.1), Conscientiousness should positively influence it (HP1.2), and Neuroticism should negatively influence RWA (HP1.3).…”
mentioning
confidence: 52%
“…If our data were comparable with those found by Van Hiel, Cornelis, and Roets (2007) and by Sibley and Duckitt (2009), Openness should negatively influence RWA (HP1.1), Conscientiousness should positively influence it (HP1.2), and Neuroticism should negatively influence RWA (HP1.3).…”
mentioning
confidence: 52%
“…There is firm evidence for the relationships between the broad bandwidth dimensions of Openness and Conscientiousness and RWA, and of Openness and Agreeableness with SDO (Sibley & Duckitt, 2008). In integrative models including broadband personality and social attitudes to explain other target variables like racism (see, for example, Ekehammar , Akrami, Gylje & Zakrisson, 2004;Van Hiel, Cornelis & Roets, 2007), broadband personality has been typically considered to be a strong basis of social attitudes, which were conceptualized as mediator variables. Zaleski et al (1995) previously found evidence that personality traits predispose social attitudes to a certain extent.…”
Section: Toward An Integrative Model Of Dispositional Variables and Pmentioning
confidence: 99%
“…The seminal work in this domain was advanced in the 1950s with the introduction of 'The Authoritarian Personality' (Adorno et al 1950). Although originally proposed as a fixed personality trait, recent accounts usually describe authoritarianism as a social-ideological attitude that might show some changeability, although it is partially driven by core personality traits (e.g., low Openness, Duckitt 2001;Cohrs, Kämpfe-Hargrave, and Riemann 2012;Sibley and Duckitt 2008;Van Hiel, Cornelis, and Roets 2007).…”
Section: Authoritarianism As a Possible Moderatormentioning
confidence: 99%